Polymorphism in the promoter region of the mannose-binding lectin gene among human T-cell lymphotropic virus infected subjects - ALVES, Anna Elizabeth Martins (2013)
The present study investigated the frequency of the mutations at positions -550 and -221 of the mannose-binding lectin (MBL) gene in a sample of 75 human T-cell lymphotropic virus (HTLV) infected patients and 96 HTLV seronegative controls, in order to evaluate the occurrence of a possible association between the polymorphism and HTLV infection. A sequence specific primer-polymerase chain reaction was used for discrimination of the polymorphism. The analysis of allele frequencies at position -550 did not show any significant differences between HTLV infected group and controls, but there was a significant difference at position -221. The comparative analysis of haplotypes frequencies were not significant, but the genotype frequencies between the two groups, revealed a higher prevalence of genotype LYLX (25.3%), associated with medium and low MBL serum levels among HTLV infected subjects. The odds ratio estimation demonstrated that the presence of genotype LYLX was associated with an increased risk of HTLV infection (p = 0.0096; 1.38 < IC95% < 7.7605). There was no association between proviral load and the promoter polymorphism, but when promoter and exon 1 mutations were matched, it was possible to identify a significant higher proviral load among HTLV infected individuals carrying haplotypes correlated to low serum levels of MBL. The present study shows that the polymorphism in the promoter region of the MBL gene may be a genetic marker associated with HTLV infection, and emphasizes the need for further studies to determinate if the present polymorphism have any impact on diseases linked to HTLV infection.